On the Solution of the Exterior Dirichlet Problem for an Axisymmetric Potential - Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For an unbounded domain of the meridian plane with bounded smooth boundary that satisfies certain additional conditions, we develop a method for the reduction of the Dirichlet problem for an axisymmetric potential to Fredholm integral equations. In the case where the boundary of the domain is a unit circle, we obtain a solution of the exterior Dirichlet problem in explicit form.